A Public Health Perspective of Women's Mental Health - Levin, Bruce Lubotsky; Becker, Marion Ann (Springer New York : Imprint: Springer, 2010)
A Public Health Perspective of Women's Mental Health Edited by Bruce Lubotsky Levin and Marion Ann Becker As many as one-half of all women in the U.S. will experience some form of mental illness in their lives-an especially distressing fact when health care budgets are in flux, adding to existing disparities and unmet health needs. Written from a unique multidisciplinary framework, A Public Health Perspective of Women's Mental Health addresses today's most pressing mental health challenges: effective treatment, efficient prevention, equal access, improved service delivery, and stronger public policy. Eminent clinicians, researchers, academicians, and advocates examine the effects of mental illness on women's lives and discuss the scope of clinical and service delivery issues affecting women, focusing on these major areas: Epidemiology of mental disorders in girls, female adolescents, adult women, and older women. Selected disorders of particular concern to women, including depression and postpartum depression, eating disorders, menopause, chemical dependence, and HIV/AIDS. Mental health needs of women in the workplace, rural areas, and prisons. Racial and ethnic disparities and their impact on service delivery. Parenting and recovery issues in mothers with mental illness. Women's mental health services in an era of evidence-based medicine. Improving women's health in today's technological climate. A Public Health Perspective of Women's Mental Health is a resource of immediate importance to professionals and graduate students in the public health, health administration, health disparities, social work, behavioral health, and health services research fields, as well as nursing, community/health psychology and community/public psychiatry.